Efektifitas Distribusi Zakat Produktif Dalam Meningkatkan Kesejahteraan Mustahik (Studi Kasus Pada BAZNAS Propinsi Sumatera Utara) - Atika Suri (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine how the distribution of productive zakat funds in BAZNAS North Sumatra Province and whether the distribution of productive zakat in improving the welfare of the beneficiaries of zakat funds (mustahik) in BAZNAS North Sumatra Province has been effective or not. This study uses a descriptive approach with the type of research being qualitative, so that the data analysis used is descriptive qualitative analysis, which is a type of research that explains or describes a situation or situation that will be studied thoroughly and in depth. Data collection techniques were carried out by field research (field research), then the tools used in this study were observation, interviews and documentation. The results of this study are that the distribution of productive zakat carried out by BAZNAS of North Sumatra Province through the North Sumatran Makmur program to recipients of zakat funds (Mustahiq) if viewed from the institutional side has been effective. Monitoring and evaluation every year. However, if viewed from the mustahik side, the results are not yet effective, because there are external factors that become obstacles, one of which is the COVID-19 pandemic. This is evidenced by the number of beneficiaries (mustahik) which amounted to 16 people, but only 2 people were still able to maintain their business.